2005
DOI: 10.1266/ggs.80.357
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal assignment and deletion mapping of barley EST markers

Abstract: From about 10000 PCR-based EST markers of barley we chose 1421 EST markers that were demonstrated to be amplified differently by PCR between wheat ( Triticum aestivum cv. Chinese Spring) and barley ( Hordeum vulgare cv. Betzes). We assigned them to the seven barley chromosomes (1H to 7H) by PCR analysis using a set of wheat-barley chromosome addition lines. We successfully assigned 701 (49.3%) EST markers to the barley chromosomes: 75 to 1H, 127 to 2H, 119 to 3H, 94 to 4H, 108 to 5H, 81 to 6H and 97 to 7H. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 40 publications
3
65
0
Order By: Relevance
“…Therefore, 24 out of 37 4HS markers (64.9%) and 39 out of 56 4HL markers (69.6%) were located in the distal regions accounting for no more than 25.6% of the 4HS arm and for no more than 43.1% of the 4HL arm, respectively. This fact suggests that EST markers or genes on chromosome 4H were more abundant in the distal region than in the proximal region, as observed for other barley chromosomes (Künzel et al, 2000;Nasuda et al, 2005;Ashida et al, 2007;Sakai et al, 2009). This trend was more obvious in the subtelomeric regions.…”
Section: Cytological Mapping Of Barley Est Markerssupporting
confidence: 59%
See 1 more Smart Citation
“…Therefore, 24 out of 37 4HS markers (64.9%) and 39 out of 56 4HL markers (69.6%) were located in the distal regions accounting for no more than 25.6% of the 4HS arm and for no more than 43.1% of the 4HL arm, respectively. This fact suggests that EST markers or genes on chromosome 4H were more abundant in the distal region than in the proximal region, as observed for other barley chromosomes (Künzel et al, 2000;Nasuda et al, 2005;Ashida et al, 2007;Sakai et al, 2009). This trend was more obvious in the subtelomeric regions.…”
Section: Cytological Mapping Of Barley Est Markerssupporting
confidence: 59%
“…PCR analysis of the dissection lines First, we checked the PCR amplification of the 93 EST markers in the control lines to confirm that the markers are specific to chromosome 4H as reported by Nasuda et al (2005), and found that 37 were located on the 4HS arm and 56 on the 4HL arm. Then, we conducted PCR analysis for the 60 dissection and four control lines using the 93 EST markers ( Table 2).…”
Section: Pcr Analysismentioning
confidence: 99%
“…These 7H deletion and translocation lines were then used for the physical mapping of the 7H barley chromosome (Serizawa et al 2001). Nasuda et al (2005), Ashida et al (2007) and Sakai et al (2009) performed deletion mapping on barley chromosomes 7H, 5H and 3H using barley dissection lines and barley-specific EST Euphytica (2014) 195:315-329 321 markers. The barley dissection lines were produced from CS-Betzes addition lines, so they all carried chromosome segments from Betzes barley.…”
Section: Chromosome Pairing In Wheat 3 Barley Hybridsmentioning
confidence: 99%
“…For example, Nasuda et al (2005) and Ashida et al (2007) mapped barley EST markers on the barley chromosome deletion stocks and estimated the physical location of these ESTs. Although the resolution in segmental allocation of markers was low in wheat deletion stock mapping (Sorrells et al, 2003), the approach is a useful first step in developing BAC contigs for genome sequencing.…”
Section: Snp Typing 17% Caps 9%mentioning
confidence: 99%